ANALISIS HUKUM TERHADAP KEWENANGAN GEGANA BRIMOB POLDA SUMATERA UTARA DALAM PENANGANAN KEJAHATAN LINTAS BATAS (CROSS-BORDER CRIMES) - Sukma Ramadansyah Ginting (NERACA KEADILAN, 2025)
Cross-border crime is a serious challenge in the era of globalization, where national borders are increasingly blurred due to technological advances and mobility. North Sumatra Province, which borders the Straits of Malacca and Malaysia, is a vulnerable area for narcotics and firearms smuggling, as well as cross-border terrorist activity. The Gegana Detachment of the Mobile Brigade Corps (Brimob) of the North Sumatra Regional Police, as the National Police's elite analytical unit, plays a crucial role in combating these crimes, particularly through its technical capabilities in bomb disposal and armed threat security. However, debate has arisen regarding the limits of this unit's legal authority to repress transnational crime. This study aims to analyze the legal basis for the Gegana Detachment's authority in handling cross-border crime, assess the effectiveness of this unit's involvement in law enforcement operations, and evaluate the coordination structure between relevant agencies. The approach used is empirical juridical, through the study of laws and regulations and direct observation in the field. This research also examines the role of Gegana as part of the rapid response system to the threat of terrorism, as well as the normative gaps that arise due to the absence of technical regulations that regulate in detail its operational authority. The research results show that although the role of Gegana is very vital in the context of security and tactical operations, its authority is still functional and legally limited. The absence of an explicit legal basis causes overlapping roles with other investigative units such as Densus 88, and raises the potential for legal doubts in the enforcement process. Therefore, regulatory reform is needed in the form of cross-institutional SOPs and strengthening of implementing regulations to ensure that every operational action has clear, effective, and accountable legal legitimacy.